The Influence of Thyroid Hormones on Levels of Lipid Profile and Adipokine in Iraqi Women with Thyroid Disorders - Abaas, Kawther; AL-Qaisi , Alaa Hussein J.; Hairunisa, Nany (Al-Nahrain Journal of Science, 2023)
Hypothyroidism and hyperthyroidism are prevalent endocrine diseases. These have significant implications for lipid synthesis, mobilization, and metabolism. Retinol-binding protein 4 is a new adipokine implicated in some physiological and pathological processes, such as metabolic and endocrine disorders. Its elevation aids in the diagnosis of thyroid problems. The present study includes 60 women with thyroid diseases; 30 of them have hypothyroidism and 30 have hyperthyroidism. This study includes 20 healthy women as a control group. For each participant anthropometric, biochemical Thyroid-stimulating hormone, triiodothyronine, Thyroxine, lipid profile, and retinol binding protein-4 are measured. The results show that hypothyroid women have significantly higher levels of total cholesterol, triglycerides, and low-density lipoprotein cholesterol as compared to the hyperthyroid or control group. The serum of total cholesterol, triglycerides, and low-density lipoprotein cholesterol are significantly lower in hyperthyroid women compared to the hypothyroid or control group. In addition, there are no significant differences in blood high-density lipoprotein cholesterol concentrations among the three groups. Furthermore, serum retinol-binding protein-4 levels were higher in the hyperthyroid group compared to the hypothyroid or control groups. According to the findings of this study, hypothyroidism causes dyslipidemia, which raises the risk of cardiovascular disease while hyperthyroidism causes abnormalities in lipid profiles. Additionally, hyperthyroidism causes an increase in serum retinol-binding protein-4 levels in the blood.